A PILOT STUDY OF ATTITUDES TOWARD INTERNET USE AND WEB ACTIVITY AMONG 16- TO 18-YEAR-OLD STUDENTS EDUCATED IN AN ARTS SCHOOL (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Purpose: to study the attitudes towards Internet use and activity in the Global Network among 16-18-year-old students from the National School of Arts, Ruse, Bulgaria.Methods: using the direct survey method in a school environment, all 105 students between the ages of 16 and 18 were surveyed. The results include the valid questionnaires, which are 101 in number. Mathematical and statistical methods for data processing with SPSS Statistics 26.0 were used. Frequency and non-parametric analysis were applied. Differences are considered statistically significant at p≤0.01. Results: In the object of study, the virtual environment is more of an option for interpersonal communication, searching for different information, shopping, and not a dominant one. Students who have developed a personal need for technology most often and for a long time stay in it. Significantly expressed statistically significant relationships were found between age and the most frequently visited sites by students, age and time spent on the Global Web, initial use of the Global Web and better understanding with Internet friends, better understanding with Internet friends and difficulties in finding a common language with others who do not use the Internet. A strongly expressed relationship was found between initial use of the Global Web and the most frequently searched for on the Internet, online shopping and the need to use the Internet, and a moderately expressed relationship - between the need to use the Internet and improved mood in online mode. Although the respondents are not only engaged in additional study of a special subject, but also a high percentage of them participate in extracurricular activities and have additional (unrelated to Internet use) interests, the established dependencies suggest that over time the risk of problematic use of the Global Web with the corresponding consequences of this is possible to increase, since half of the students have risky influences in terms of Internet consumption. Conclusions: To reduce the risk of problematic use of the Global Network, it is recommended to systematically implement preventive actions based on a complex of informational, emotional-evaluative and behavioral components.